(untitled) (American Journal of Smart Technology and Solutions, 2025)
The simultaneous application of Remote Sensing technology with GIS mapping technologies and Precision Agriculture presents effective solutions to protect sustainable farming practices and climate-resistant measures particularly in the sensitive environment of Bangladesh. This investigation combines the technologies to improve resource allocation while tracking farm health and tuning agricultural operations for Bangladesh’s climate-distinctive environment. Through remote sensing data collection and GIS spatial analytics the research delivers operational insights which assist with soil analysis and water control as well as agricultural productivity assessment in all regions of Bangladesh. This integration receives support from precision agriculture tools which use variable-rate technologies together with IoT devices to deliver site-specific interventions that fit Bangladesh’s agricultural geography. The research shows important outcomes regarding resource conservation because the adoption of advanced techniques has reduced water consumption as well as fertilizer use by twenty-five percent and crop stress detection improved yield estimates by eighteen percent. Through analysis the research distinguishes both high-risk locations for droughts and floods and provides strategic methods to protect them. The research demonstrates how technology-based methods are essential for climate-smart agriculture through insights that create a direction for Bangladesh officials and practitioners to improve food security and climate resilience.